Stakeholders, conservation and socio-economic development: the case of Mapungubwe Cultural Landscape World Heritage Site, South Africa - Taruvinga, Pascall (Department of Archaeology, 2019)
The strategic importance of World Heritage sites in addressing social needs is now well recognised in Africa and elsewhere. However, the contribution of these sites to socio-economic development is rarely a topic of empirical investigation and is mostly implied. It is in this context that research was performed on stakeholder-driven conservation and socio-economic development processes, using Mapungubwe Cultural Landscape World Heritage Site (South Africa) as the case study. The study solicited the views and opinions of 243 participants, using a dynamic and mixed methodology which combined desktop studies, questionnaire surveys, interviews and Delphi techniques. This mixed methodology was premised on the Multiple-Multi-Layered Stakeholder Theory (MMST). The main findings of the thesis are that conservation and socio-economic development are equally important and should co-exist as stakeholder-driven processes at Mapungubwe Cultural Landscape World Heritage Site (MCLWHS). This supports the notion of caring for the well-being of both heritage and society. The study also established that, while there are benefits associated with World Heritage, the lack of credible statistics and the absence of monitoring indicators mean that its contribution to socio-economic development is not quantified. In addition, the study reveals that, while Mapungubwe Cultural Landscape World Heritage Site (MCLWHS) has multiple stakeholders with different expectations and levels of power, these are not involved in the decision-making processes at the site. This creates challenges that impede the full realization of both conservation and socio-economic benefits at MCLWHS, which can only be addressed through adaptive management supported by creativity and innovation embedded in multi-pronged strategies. The results motivate for adoption of adaptive management approaches, “learning by doing”, as opposed to a monolithic adherence to State-Based Management Systems. An adaptive approach promotes better communication flow between decision makers and all other stakeholders to ensure stakeholder-driven conservation and socio-economic development at World Heritage sites. Neither conservation nor socio-economic development plan for each other at World Heritage sites, yet both cannot be disassociated from their broader environment and related stakeholders. The study concludes that World Heritage governance should be about managing continuity and change as influenced by multiple stakeholders who are the beneficiaries of both conservation and developments at heritage sites. World Heritage has potential to contribute massively to socio-economic development in and around host communities without eroding its credibility and integrity.